L'enquête publique préalable à la décision comme modèle alternatif - Lemieux, Pierre (Les Cahiers de droit, 1983)
Problems relating to individual and group involvement in the administrative decision making process, its opportunity, modalities and efficiency are illustrated in the context of preliminary public inquiries that precede legislative decisions. This study focuses on the public's involvement in the application of government decisions. This is illustrated by two specific examples : the inquiry before the Bureau d'audiences publiques sur l'environnement and the proposed new public consultation policy of the A tomic Energy Control Board of Canada.